(untitled) (Journal of Academic Research, 2024)
The research aimed to identify the professional and ethical characteristics of the performance of faculty members in Libyan universities in light of the standards of professional and ethical performance of university professors, and whether there are differences due to the variables (gender - specialization - academic qualification - academic degree - years of experience) for a sample of (424) faculty members. Teaching from public Libyan universities.